Living With Spasticity During the COVID‐19 Pandemic: A Qualitative Study of Patient, Carer and Physician Experiences - Mohamed Sakel; Karen Saunders; Rafey Faruqui; Jamie Keene; David Wilkinson (Wiley, 2024)
ABSTRACT Background Approximately 4.4 million people in England (8% of the total population) are living with a long‐term neurological condition. Within this group of vulnerable individuals, there will be individuals living with severe spasticity that requires regular outpatient treatment with botulinum toxin injection. The closure of outpatient spasticity services during the pandemic impacted individuals who required spasticity treatment and their carers, as well as the specialist clinicians responsible for service delivery. Objectives We aimed to gain insight into the experiences of individuals living with spasticity, their carers and a clinical spasticity service lead during the pandemic, and to reflect on potential learning for the future. Methods A qualitative study was designed using semi‐structured interviews conducted by telephone. Participants comprised patients living with a long‐term neurological condition who attended outpatient spasticity clinics before the start of the pandemic in England, primary carers who accompanied patients attending these clinics and a clinical spasticity service lead. Data were audio recorded, transcribed, anonymised and coded. Data analysis utilised the One Sheet of Paper thematic approach to identify themes, which were discussed and analysed by the interdisciplinary research team and two patient and carer participants. Results Out of the 11 participants recruited, aged 36-77 years, seven comprised people living with spasticity related to a long‐term neurological condition, three were carers and one was a clinical spasticity service lead. Six participants were male and five were female. Among the participants, four were stroke survivors, two were living with spinal cord injury and one was living with multiple sclerosis. Analysis revealed six major themes: experience of living with spasticity during the pandemic; impact of the pandemic on patient, carer and clinician health; access to and experience of outpatient clinic appointments; coping strategies during the pandemic; system improvements; and learning from the pandemic period. Conclusion These findings contribute research knowledge to a very limited research knowledge base and suggest that there is scope for improving system and service delivery through the allocation of research funding to senior clinicians working in this specialist area.